1995
DOI: 10.1128/iai.63.4.1340-1348.1995
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella haemolytica serotype 2 contains the gene for a noncapsular serotype 1-specific antigen

Abstract: An ssa1-homologous genomic fragment cloned from Pasteurella haemolytica serotype 2 (ST2) enabled transformation of Escherichia coli DH5␣ to a serotype 1 (ST1) phenotype through expression of the ST1-specific antigen (Ssa1). The Ssa1 protein expressed by ssa1-transformed E. coli was susceptible to heat and protease treatment and was distinct from P. haemolytica ST1-specific capsular polysaccharide. Electrophoretic analysis of in vitro-translated proteins, as well as the predicted amino acid sequence, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Due to the presence of serotype 1-specific antigen (ssa1) gene, the commensal M. haemolytica strains may become pathogenic to their host in stress-prevailing environments. Moreover, a genetic correlation between ssa1 and leukotoxin (lkt) indicates that the PHSSA could have a significant pathobiological effect in the progression of pneumonic pasteurellosis (22,23). Therefore, the PHSSA represents a species-specific and virulence-associated gene of M. haemolytica.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of serotype 1-specific antigen (ssa1) gene, the commensal M. haemolytica strains may become pathogenic to their host in stress-prevailing environments. Moreover, a genetic correlation between ssa1 and leukotoxin (lkt) indicates that the PHSSA could have a significant pathobiological effect in the progression of pneumonic pasteurellosis (22,23). Therefore, the PHSSA represents a species-specific and virulence-associated gene of M. haemolytica.…”
Section: Discussionmentioning
confidence: 99%
“…This selective growth and colonization of the URT by ST1 is a prerequisite for the onset of BPP. The specific bacterial and host factors mediating this shift from ST2 and ST4 to ST1 are not clear, although the surface-expressed ST1-specific factor of M. haemolytica ST1 may promote selective colonization of the URT by this bacterium (Gonzalez et al, 1995). Once present at high levels in the URT, ST1 enters the alveolar spaces through repeated aspiration of infected droplets and sloughed cells/tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the localization and processing of the homologues in S. marcescens, other proteins that are outer surface membrane proteins in different genera provide a hint. They are the 120 kDa surface antigen (rOmpB) in R. rickettsii (27,28), whose COOH-terminal portion shows 19% identity in amino acid sequence to that of the homologues, and the 100 kDa serotype-specific antigen (Ssal) of P. haemolytica (29,30), which shows significant homology (25% identity) to pre-proSSP and the SSP homologues over the entire sequence. The precursor of rOmpB is composed of an NH,-terminal signal peptide, a mature part, and a COOH-terminal prodomain.…”
Section: Discussionmentioning
confidence: 99%
“…A computer-aided homology search revealed that the COOH-terminal pro-domain of the 120 kDa protein (rOmpB) of Rickettsia rickettsii (27,28) showed 19% identity in amino acid sequence to that of the SSP homo-logues. Moreover, the serotype-specific antigen (Ssal) of Pasteurella haemolytica (29,30), which was identified as a 100 kDa outer membrane protein, showed significant homology (25% identity) to preproSSP and the SSP-homologues over the entire sequences. The alignment is also shown in Fig.…”
Section: Distribution Of Nucleotide Sequences Homologous With the Regmentioning
confidence: 99%